Biogas in the suburbs: An untapped source of clean energy?. (1st April 2019) - Alexander, Samuel; Harris, Peter; McCabe, Bernadette K.
Abstract: This article explores the potential of producing domestic, home-scale biogas using anaerobic digestion in the suburbs of the developed world – an urban context where currently biogas production is almost non-existent. The current status of food waste management across the globe shows that internationally, cities are increasingly using anaerobic digestion as a central technology at commercial scale to treat food waste and decarbonise through the recovery of energy and nutrients. However, in order to achieve this, it is preferable to separate organic waste such as food waste from other waste streams. Australia currently does not offer any schemes that support source separation of household food waste. Notwithstanding this, there are upwards of five large-scale plants currently treating commercial food waste and substantial scope exists to increase this provided appropriate waste management strategies are put in place. Nevertheless, the absence of food waste management schemes in developed countries may provide an impetus for individuals in urban landscapes to explore the potential of home-style biogas systems to produce energy and biofertiliser using food waste derived from households. This article provides a novel case study of one operator's experience using a domestic system, the 'HomeBiogas 1.0' unit, in the suburbs of Melbourne, Australia. A critical analysis of the system was performed, including a cost benefit analysis of the recently released 'HomeBiogas 2.0' unit. The cost benefit analysis indicated that the system could pay for itself in 4.45 years if simply mitigating the cost of natural gas. This payback period is likely to be reduced if the value of fertiliser were included or if use of a HomeBiogas unit allows for disconnection from the gas grid (avoiding service fees), as it did in this case study. The paper concludes by identifying barriers from a technical, regulatory and education perspective. Highlights: The potential for domestic scale biogas in urban landscapes was examined. A unit located in the suburbs of an Australian capital city was assessed. Cost benefit analysis resulted in an approximate payback period of 4.45 years. Barriers from a technical, regulatory and education perspective were identified.